The Gap Between Public Perception and Scientific Advancements Endangers Humanity - Gurevitz, Michael (European Journal of Applied Sciences, 2023)
Homo-sapiens is considered the top organism in the animal kingdom due mostly to his developed brain (neocortex in particular), and cognitive, communicative, and spiritual abilities. Yet, further contemplation uncovers weaknesses and risks ensuing his remarkable evolutionary process. On the one hand, a highly sophisticated mammal able to adopt to almost every habitat on Earth, withstand various diseases, grow his food, and develop advanced scientific and cultural infrastructures.